2013
DOI: 10.1016/j.autneu.2013.05.444
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of methods used for the assessment of autonomous nervous system's function

Abstract: Some tests that assess HRV showed adequate reproducibility. This study allows the determination of a sample size calculation for longitudinal or drug-testing studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
2
10
1
1
Order By: Relevance
“…Numerous studies have been performed to test the reliability of short-term HRV (5 min) in non-HD populations. These studies have shown poor reliability [26][27][28][29] presumably related to higher short-term variability like our data. Whether such variability carries a predictive value for major clinical events cannot be addressed by our study because no IME did occur in our cohort.…”
Section: Discussioncontrasting
confidence: 59%
“…Numerous studies have been performed to test the reliability of short-term HRV (5 min) in non-HD populations. These studies have shown poor reliability [26][27][28][29] presumably related to higher short-term variability like our data. Whether such variability carries a predictive value for major clinical events cannot be addressed by our study because no IME did occur in our cohort.…”
Section: Discussioncontrasting
confidence: 59%
“…Indeed, previous studies failed to demonstrate any changes in this important oxidant enzymatic defense [23,24,30]. A number of studies have shown an autonomic imbalance in people with diabetes with alterations in time domain components, with lower SDNN and PNN50 [31,32], as well as lower oscillations in HF components that reflect parasympathetic tone, and a marked prevalence in sympathetic tone, evaluated by LF components [10,12,33]. In accordance with previous studies, we found a significant reduction in time domain components (means RR and SDNN) at baseline, but no changes in LF or HF components.…”
Section: Baseline Measurementsmentioning
confidence: 99%
“…Increased sympathetic and/or decreased parasympathetic activities have been associated with high risk of sudden death. Indeed, several studies have shown that patients with T1DM and T2DM showed autonomic dysfunction [10][11][12]. Interestingly, most studies have focused on patients with T2DM and only a few studies have investigated T1DM and autonomic dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…These studies indicated that inconsistent results can be expected with data sampling at different times of the day [25], presence of heart disorders or unhealthy participants [25,28], gender differences [26], or when different HRV indicators are used for monitoring the autonomic system [26].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in humans showed that standardization of methodology is important to assure inter-and intra-study repeatability of HRV measurements [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%